Processes of the Development of Terrorism and the Main Trends in the Fight Against it in Uzbekistan - Zafarovich, Kamilov Davron (European Journal of Life Safety and Stability (2660-9630), 2022)
the article is devoted to the analysis of the emergence and development dynamics of terrorism based on religious rhetoric formed in the last quarter of the XX century and the beginning of the XXI century, in which the events are researched in chronological order based on the information of the global terrorism index and other organizations. Also, the information on the internal political and social reforms of New Uzbekistan in the fight against terrorism and the framework of international organizations and inter-period cooperation was systematically analyzed.